Resiliensi dan Penerimaan Diri Tokoh Utama Novel Timun Jelita Karya Raditya Dika: Kajian Psikologi Sastra - Adiat Yusuf Kurnianto; Mulasih Mulasih; Eko Sri Israhayu; Onok Yayang Pamungkas; Akhmad Fauzan (Jurnal Pendidikan Indonesia, 2026)
This study aims to explain the resilience and self-acceptance of the main character in the novel Timun Jelita, written by Raditya Dika, using a literary psychology approach. Literary works not only reflect social conditions but also contain the psychological dynamics of characters that can be analyzed scientifically. This novel was chosen because it is a work that has not been extensively studied, particularly from a literary psychology perspective. The method used in this study is qualitative descriptive, employing data collection techniques such as documentary analysis, note-taking, and literature review. Primary data sources were drawn from the novel Timun Jelita, while secondary data sources were obtained from relevant books, journals, and studies. Data analysis was conducted using Sigmund Freud’s psychoanalytic theory (id, ego, superego), the resilience theory by Reivich and Shatté, and the concept of self-acceptance by Supratiknya. The findings indicate that the main character possesses the ability to cope with life’s pressures through emotional regulation, optimism, empathy, self-confidence, and the capacity to identify new opportunities. Additionally, the main character also demonstrates self-acceptance through an open attitude, acceptance of others, and better mental health. This study contributes to expanding the field of psychology-based Indonesian literary studies